COMMUNICATING SAFETY AND HYGIENE LEVEL POST COVID-19 IN AVIATION: DIGITAL MARCOMM STRATEGY OF SINGAPORE AIRLINES - Daniel Susilo; Carl C.G. Dizon (Lafadz Jaya Publisher, 2023)
Singapore Airlines is part of airlines industry, they offer wide range of service and product in modern times. Digital marketing nowadays plays a crucial role for industry and the company itself. Through Singapore Airlines @singaporeair’s Instagram account we can see how they prioritize safety product and healthy service and the content analysis method validate it. This means that Singapore Airlines prioritize connecting themselves with their customer and thinks the best for them. By digital marketing we can se it can change someone’s life.